PENGEMBANGAN PUSAT KEGIATAN WARGA ASEM PAYUNG KEL. GEBANG PUTIH SURABAYA - Josephine Roosandriantini; Lucia Ina Trisjanti; Y.A. Widriyakara Setiadi; Anas Hidayat; Stefanus Prabani Setio; Heristama Anugerah Putra (LPPM UNIVERSITAS HASYIM ASY'ARI TEBUIRENG JOMBANG, 2022)
The Gebang Putih area is a fairly densely populated settlement because each residence does not have an open yard. The activities of the youth or local residents are limited to gathering at locations outside the RW 003 environment. The results of observations and interviews with community leaders in RT. 02, it was found that residents of RW 003 needed a place for sports activities, gatherings, and discussions for residents of RW 003. The purpose of this community service was so that residents had a new activity center that was able to accommodate gathering, exercise, and socializing activities. This community service is expected to enable residents to carry out activities in a sustainable manner around their homes, thereby creating a friendly atmosphere and increasing a sense of brotherhood and harmony among residents. Community service activities carried out were utilizing the sewer side as a place for sports activities, and discussions for residents of RW 003. The method used was an observation, and interviews with the chairman of RW 003 and also residents of 003 Asem Umbrella. As a result of this community service, Asem Payung RW 003 village has infrastructure for joint activities between residents, such as ping pong, table tennis, or a gathering area.